Sculpting the End of Time: The Anamorphosis of History and Memory in Andrei Tarkovsky’s Mirror (1975) - Nelson, Tollof (Cinémas)

(untitled) (Cinémas, 2003)
AbstractArticulating a materialist conception of rhythm and temporality in the medium of film, this paper seeks to explore the way in which Andrei Tarkovsky’s Mirror (1975) is constituted by the alternation of explosions and implosions of historical time-images. The author makes a detailed analysis of several sequences of the film in order to lend support to the central argument: that spectators are taken “out of time” through an anamorphic experience of death in the material contact transmitted by a spectral dimension of history and memory. This argument allows political considerations regarding the mediation of social memory and mourning and also epistemological considerations regarding the critique of traditional historiography and the literary bias of narrative storytelling.